Periapical lesions decrease insulin signal and cause insulin resistance - Astolphi, Rafael Dias [UNESP]; Curbete, Mariane MacHado [UNESP]; Colombo, Natalia Helena [UNESP]; Shirakashi, Daisy Jaqueline [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Prieto, Annelise Katrine Carrara [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Ervolino, Edilson [UNESP]; Sumida, Doris Hissako [UNESP] (Elsevier, 2013)
Introduction: Inflammatory cytokines are associated with decreased insulin signal transduction. Moreover, local oral inflammation, such as that accompanying periodontal disease, is associated with insulin resistance and type 2 diabetes mellitus. The aim of this study was to evaluate the effect of periapical lesions (PLs) on insulin signaling and insulin sensitivity in rats. We hypothesized that PLs alter systemic insulin signaling and insulin sensitivity via elevated plasmatic tumor necrosis factor α (TNF-α). Methods: Wistar rats were divided into control (CN) and PL groups. PLs were induced by exposing pulpal tissue to the oral environment. After 30 days, insulin sensitivity was measured using the insulin tolerance test. After euthanization, maxillae were processed for histopathology. Plasmatic concentrations of tumor necrosis factor α (TNF-α) were determined via the enzyme-linked immunosorbent assay. Insulin signal transduction was evaluated using insulin receptor substrate tyrosine phosphorylation status and serine phosphorylation status in periepididymal white adipose tissue via Western blotting. For insulin signaling and insulin tolerance tests, the analyses performed were analysis of variance followed by the Tukey post hoc test. For TNF-α analysis, the Student's t test was used. In all tests, P <.05 was considered significant. Results: The rats with PLs showed higher plasmatic TNF-α, lower constant rate for glucose disappearance values, and reduced pp185 tyrosine phosphorylation status but no change in serine phosphorylation status in white adipose tissue after insulin stimulation. Conclusions: PLs can cause alterations to both insulin signaling and insulin sensitivity, probably because of elevation of plasmatic TNF-α. The results from this study emphasize the importance of the prevention of local inflammatory diseases, such as PLs, with regard to the prevention of insulin resistance. Copyright © 2013 American Association of Endodontists.
Keywords: Diabetes mellitus; insulin resistance; periapical lesions; tumor necrosis factor α